Teaching Vocabulary Through Cartoon Films For Toddlers By Using Mind Mapping Technique - Sara Frimaulia; Irhamni (LPPM STKIP AL MAKSUM, 2021)
This paper intends to explore the connection between vocabulary development and cartoon movies, specifically focusing on how cartoon movies can be effectively utilized to teach vocabulary. Vocabulary encompasses a collection of words that convey a wide array of meanings. Cartoons, although primarily designed for children's entertainment, can also serve as valuable educational tools. With the objective of establishing the correlation between cartoons and education, the author has produced a research paper titled